2017
DOI: 10.1038/s41598-017-03507-0
|View full text |Cite
|
Sign up to set email alerts
|

Giant Magnetic Band Gap in the Rashba-Split Surface State of Vanadium-Doped BiTeI: A Combined Photoemission and Ab Initio Study

Abstract: One of the most promising platforms for spintronics and topological quantum computation is the two-dimensional electron gas (2DEG) with strong spin-orbit interaction and out-of-plane ferromagnetism. In proximity to an s-wave superconductor, such 2DEG may be driven into a topologically non-trivial superconducting phase, predicted to support zero-energy Majorana fermion modes. Using angle-resolved photoemission spectroscopy and ab initio calculations, we study the 2DEG at the surface of the vanadium-doped polar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…The AFM coupling was also observed for the layered magnetically-doped BiTeI 44 , 45 , for layered RE-Rh 2 Si 2 systems (where RE is Gd, Ho) 41 and for recently discovered magnetically-ordered stoichiometric AFM TI MnBi 2 Te 4 32 , 33 , 46 , where the magnetic coupling is provided by an AFM coupling between the magnetic Mn atoms in the neighbor quintuple layers with alternating magnetic moments 47 . Inside each magnetic layer the magnetic coupling is ferromagnetic.…”
Section: Methodsmentioning
confidence: 64%
“…The AFM coupling was also observed for the layered magnetically-doped BiTeI 44 , 45 , for layered RE-Rh 2 Si 2 systems (where RE is Gd, Ho) 41 and for recently discovered magnetically-ordered stoichiometric AFM TI MnBi 2 Te 4 32 , 33 , 46 , where the magnetic coupling is provided by an AFM coupling between the magnetic Mn atoms in the neighbor quintuple layers with alternating magnetic moments 47 . Inside each magnetic layer the magnetic coupling is ferromagnetic.…”
Section: Methodsmentioning
confidence: 64%
“…In earlier works, devoted to experimental and theoretical study of V-doped BiTeI 9 , 28 , it was shown that the KP gap reaches the value of ~ 90 meV with the V concentration of 2%. Remarkably, the ab-initio calculations reveal KP gap no greater than 34 meV in this case 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In earlier works, devoted to experimental and theoretical study of V-doped BiTeI 9 , 28 , it was shown that the KP gap reaches the value of ~ 90 meV with the V concentration of 2%. Remarkably, the ab-initio calculations reveal KP gap no greater than 34 meV in this case 9 . This discrepancy could be related to unaccounted Bi-vacancies in the vicinity of V impurities, which can affect the magnetic moments of the nearest Te atoms and increase the gap value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetization has to be directed perpendicular to the sample surface to open the gap in all k . The spin structure of the state becomes "hedgehog"-shape in the vicinity of the KP and the electronic structure can be tuned to have one circular Fermi contour 9 . Similar spin degeneracy lifting can be observed in magnetic topological insulators for the topological surface state [10][11][12][13][14][15] or Rashba-like state 16 .…”
Section: Introductionmentioning
confidence: 99%